2018
DOI: 10.11591/edulearn.v12i3.7278
|View full text |Cite
|
Sign up to set email alerts
|

Developing STEM Based Student’s Book for Grade XII Biotechnology Topics

Abstract: The study aims to develop a valid, practical and effective Biology student's book based on Science Technology Engineering and Mathematics (STEM) on the topic of biotechnology for Grade XII. The method applied for the study was research and development with the 4-D model. The subjects were 58 Grade XII students of SMAN 1 Muncar, Banyuwangi-Indonesia. The results showed that the average of validation result of STEM-based student's book was 86.4% which fell under a strong valid category. The average percentage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 1 publication
2
14
0
5
Order By: Relevance
“…In the construct of attitude concentration, data was listed at a higher-level scale, because respondents responded with neither disagree or agree, agree, and strongly agree (3-5 Likert 'scale). The concentration distribution of the construct of the application (the overlap color) was at the level of a neutral scale, namely disagree, neither disagree or agree, and agree (2)(3)(4). This form showed that, even though these science teachers have implemented STEM lessons in the classroom, these same teachers do not have a good knowledge about STEM education.…”
Section: Descriptive Datamentioning
confidence: 99%
See 4 more Smart Citations
“…In the construct of attitude concentration, data was listed at a higher-level scale, because respondents responded with neither disagree or agree, agree, and strongly agree (3-5 Likert 'scale). The concentration distribution of the construct of the application (the overlap color) was at the level of a neutral scale, namely disagree, neither disagree or agree, and agree (2)(3)(4). This form showed that, even though these science teachers have implemented STEM lessons in the classroom, these same teachers do not have a good knowledge about STEM education.…”
Section: Descriptive Datamentioning
confidence: 99%
“…In Indonesia, teachers have been shown to mainly obtain information about STEM education from other education experts who are in college [4]. The deployment of the information to teachers incorporates various methods, including lectures, conferences, workshops, printed and electronic media, and various social media.…”
Section: The State Of the Problemmentioning
confidence: 99%
See 3 more Smart Citations